MicroRNA-320 regulates autophagy in retinoblastoma by targeting hypoxia inducible factor-1α - Liang, Yong (Exp Ther Med, 2017)
Retinoblastoma (RB) is the most common malignancy in children. Due to refractory mechanisms of chemoresistance and the toxicity of chemotherapies, novel therapies for RB treatment are urgently required. MicroRNA-320 (miR-320) is believed to be associated with the tumorigenesis of RB, although the mechanism remains unclear. Considering the hypoxic intratumoral region, the roles of miR-320 and hypoxia inducible factor-1α (HIF-1α) in the regulation of autophagy were investigated in 30 human RB samples and WERI-RB1 cells. The results demonstrated that HIF-1α was the downstream target of miR-320, and decreased miRNA-320 or HIF-1α lead to the inhibition of autophagy in WERI-RB1 cells. Compared with WERI-RB1 cells that were not transfected, silenced HIF-1α caused a 1.41-fold increase (P<0.01) in p62, a 2.71-fold decrease of Beclin1, and inhibited miRNA-320. Silenced HIF-1α also resulted in 7.29- and 7.43-fold increases in phosphorylated-mechanistic target of rapamycin (mTOR) and mTOR, respectively. In conclusion, the present results suggest that miRNA-320 may regulate the development of autophagy by targeting HIF-1α and autophagy-related proteins in RB under hypoxic conditions.